Effect of rotational speed on the interface properties of friction-welded AISI 304L to 4340 steel - Ozdemir, N.; Sarsilmaz, F.; Hascalik, A. (Elsevier Sci Ltd, 2007)
The aim of this study is to investigate experimentally the interface properties in terms of rotational speed in friction-welded AISI 304L to AISI 4340 alloy steel. Friction welding was conducted with five different rotational speeds using a direct-drive type friction welding machine. Friction pressure, forging pressure, friction time and forging time are fixed. The integrity of joints was investigated by scanning electron microscopy, while the mechanical properties assessments included microhardness and tensile tests. The experimental results showed that the thickness of full plastic deformed zone (FPDZ) formed at interface reduce as a result of more mass discarded from the welding interface with increase of the rotational speed. It was also observed that the width of the FPDZ has a important effect on the tensile strength of friction-welded samples and the tensile strength increases with increase of the rotational speed. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: friction welding; interface properties; AISI 304L stainless steel; AISI 4340 steel